Contrasting activity patterns determined by BrdU incorporation in bacterial ribotypes from the Arctic Ocean in winter - Galand, Pierre E.; Alonso-Saez, Laura; Bertilsson, Stefan; Lovejoy, Connie; Casamayor, Emilio O. (Frontiers in Microbiology, 2013)
The winter Arctic Ocean is one of the most unexplored marine environments from a microbiological perspective. Heterotrophic bacteria maintain their activity at a baseline level during the extremely low energy conditions of the winter, but little is known about the specific phylotypes that have the potential to survive and grow in such harsh environment. In this study, we aimed at identifying actively growing ribotypes in winter Arctic Ocean seawater cultures by experimental incubations with the thymidine analogue bromodeoxyuridine (BrdU), followed by immunocapturing, terminal restriction fragment length polymorphism (TRFLP) fingerprinting, cloning and sequencing the 16S rRNA gene. We incubated water collected at different months over the Arctic winter and showed that the actively growing bacterial fraction, taking up BrdU, represented only a subset of the total community. Among the BrdU-labeled bacterial taxa we identified the Flavobacteria Polaribacter, the Alphaproteobacteria SAR11, the Gammaproteobacteria Arctic 96B-16 cluster and, predominately, members of Colwellia spp. Interestingly, Colwellia sequences formed three clusters (93 and 97% pairwise 16S rRNA identity) that contributed in contrasting ways to the active communities in the incubations. Polaribacter, Arctic 96B-16 and one cluster of Colwellia were more abundant in the active community represented by the BrdU labelled DNA. In contrast, SAR11 and two other Colwellia clusters were underrepresented in the BrdU labelled community compared to total communities. Despite the limitation of the long incubations needed to label slow growing arctic communities, the BrdU approach revealed the potential for active growth in low-energy conditions in some relevant groups of polar bacteria, including Polaribacter and Arctic 96B-16. Moreover, under similar incubation conditions, the growth of different Colwellia ribotypes varied, suggesting that related clusters of Colwellia may have distinct metabolic features.